2016
DOI: 10.1074/jbc.m116.745851
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate and Heparin Promote Faithful Prion Replication in Vitro by Binding to Normal and Abnormal Prion Proteins in Protein Misfolding Cyclic Amplification

Abstract: Edited by Paul FraserThe precise mechanism underlying the conversion of normal prion protein ( Sc by using a modified PMCA performed with baculovirusderived recombinant PrP (Bac-PrP) as a substrate. The addition of heparan sulfate (HS) or its analog heparin (HP) restored the conversion efficiency in PMCA that was inhibited through nucleic acid depletion. Moreover, the PMCA products obtained under these conditions were infectious and preserved the properties of the input PrP Sc . These data suggest that HS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Why did unglycosylated ME7 prion aggregates assemble as highly stable, large parenchymal plaques? HS serves as an extracellular scaffold (73)(74)(75) and is widely recognized to bind prion aggregates, both in vitro and in vivo (76)(77)(78)(79). In accordance with these observations, we found that HS localizes to parenchymal plaques, but not to diffuse aggregates within the same brain.…”
Section: Methodssupporting
confidence: 89%
“…Why did unglycosylated ME7 prion aggregates assemble as highly stable, large parenchymal plaques? HS serves as an extracellular scaffold (73)(74)(75) and is widely recognized to bind prion aggregates, both in vitro and in vivo (76)(77)(78)(79). In accordance with these observations, we found that HS localizes to parenchymal plaques, but not to diffuse aggregates within the same brain.…”
Section: Methodssupporting
confidence: 89%
“…Therefore, we investigated whether PrP with a deletion from residues 91 to 104 or PrP∆91–104, could be converted into PrP Sc ∆91–104 after infection with BSE prions but not RML prions. To this end, baculovirus-derived recombinant mouse WT PrP and PrP∆91–104 were produced and subjected to an in vitro PMCA assay with brain homogenates from RML-, BSE- and 22L-infected, terminally ill WT mice in the presence or absence of digitonin and heparin, both of which are known to enhance conversion of PrP C into PrP Sc in PMCA [ 17 , 18 ]. The resulting PMCA products in each round were investigated for PrP Sc and PrP Sc ∆91–104 after digestion with PK in western blotting with T2 anti-PrP antibody, which recognizes residues 132–156 and 212–217 of mouse PrP [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is possible that residues 91–106 may also be involved in the structural stability of PrP C , preventing PrP C from becoming structurally unstable enough to form autonomous aggregates. Heparin has been also reported to enhance the conversion of PrP C into PrP Sc in PMCA [ 18 ]. Heparin binds to residues 23–52, 53–93 and 110–128 of PrP C and to the PK-resistant core of PrP Sc via sulfated groups [ 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEPP1 encodes for selenoprotein P, a protein which binds heparin and defends against oxidative stress and DNA damage (Burk and Hill, 2005). Heparin is a sulfated glycan previously shown to bind PrP D (Hijazi et al, 2005) and enhance prion conversion (Imamura et al, 2016; Yokoyama et al, 2011); thus, low levels of SEPP1 transcripts may be associated with altered levels of heparin and prion misfolding. Further investigations into the role of selenoprotein P in prion permissiveness are pending.…”
Section: Discussionmentioning
confidence: 99%